A Polymer Interfacial Modifier Synthesized by Living Anionic Polymerization: Incorporation of Inorganic Blocks to Chain Ends. Issue 12 (25th January 2017) - Yamamoto, Kentaro; Hirai, Tomoyasu; Oda, Yukari; Kawaguchi, Daisuke; Matsuno, Hisao; Tanaka, Keiji
Abstract : An interfacial modifier, poly(methyl methacrylate) (PMMA) having inorganic blocks at the chain ends, is prepared by living anionic polymerization. It is preferentially segregated in the mixture of PMMA to regulate the surface wettability and functions, which depend on the fed ratio. The effect of the interfacial modifications is clearly demonstrated in the cell proliferation behaviors on PMMA films. Abstract : As a polymer interfacial modifier, poly(methyl methacrylate) (PMMA) terminated with elemental blocks of polyhedral oligomeric silsesquioxane (POSS) has been exploited through the phenomenon of preferential segregation in PMMA films. The modifier synthesized by living anionic polymerization using a bifunctional initiator is segregated at the surface in the mixture of PMMA due to a "buoy" effect of the POSS blocks. This further results in the surface wettability of PMMA being regulated on the basis of the amount of the modifier fed into the matrix. Finally, it is shown that the amount of the modifier in the PMMA films affects the cell proliferation behavior via the wettability.